Ex vivo and in vivo evidence that cigarette smoke-exposed T regulatory cells impair host immunity against Mycobacterium tuberculosis - Bai, Xiyuan; Verma, Deepshikha; Garcia, Cindy; Musheyev, Ariel; Kim, Kevin; Fornis, Lorelenn; Griffith, David E.; Li, Li; Whittel, Nicholas; Gadwa, Jacob; Ohanjanyan, Tamara; Eggleston, Matthew J.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
A strong epidemiologic link exists between cigarette smoke (CS) exposure and susceptibility to tuberculosis (TB). Macrophage and murine studies showed that CS and nicotine impair host-protective immune cells against Mycobacterium tuberculosis (MTB) infection. However, little is known about how CS may affect immunosuppressive cells with MTB infection. Since CS and nicotine may activate T regulatory cells (Tregs), we investigated whether CS-exposed Tregs could exacerbate MTB infection in coculture with human macrophages and in mice that underwent adoptive transfer of Tregs from CS-exposed mice. We found that exposure of primary human Tregs to CS extract impaired the ability of unexposed human macrophages to control an MTB infection by inhibiting phagosome-lysosome fusion and autophagosome formation. Neutralizing CTLA-4 on the CS extract-exposed Tregs abrogated the impaired control of MTB infection in the macrophage and Treg co-cultures. In Foxp3 + GFP + DTR + (Thy1.2) mice depleted of endogenous Tregs, adoptive transfer of Tregs from donor CS-exposed B6.PL(Thy1.1) mice with subsequent MTB infection of the Thy1.2 mice resulted in a greater burden of MTB in the lungs and spleens than those that received Tregs from airexposed mice. Mice that received Tregs from donor CS-exposed mice and infected with MTB had modest but significantly reduced numbers of interleukin-12-positive dendritic cells and interferon-gamma-positive CD4 + T cells in the lungs, and an increased number of total programmed cell death protein-1 (PD-1) positive CD4 + T cells in both the lungs and spleens. In conclusion, CS-exposed Tregs further enhances proliferation of MTB in macrophages and in vivo, CS-exposed Tregs impair host immunity against MTB.